Research on friction and wear properties of high temperature anti-wear NiCrAlY/Co coating - YANG Rongqian; CUI Gongjun; YOU Shiquan; FENG Xiaogang; LIU Yusong (Jixie qiangdu)
In order to improve the high temperature wear resistance and extend its service life of 304 stainless steel, the high temperature wear-resistant NiCrAlY/Co coating was prepared on the surface of 304 stainless steel by the laser cladding.The morphology, phase composition and microhardness of the coating were analyzed.The tribological properties of 304 stainless steel and NiCrAlY/Co coating at different temperatures（the room temperature to 800 ℃) were studied, and the wear mechanism was analyzed.The results show that the coating is metallurgically bonded to the 304 stainless steel substrate; the coating is mainly composed of γ-Co,(Cr, Ni) and AlNi3 phases; the average microhardness of the coating（303 HV) is about 1.6 times that of the substrate（194 HV); Compared with the substrate, the coating has a smaller friction coefficient at 200-600 ℃, the friction coefficient is comparable at 800 ℃, and the lowest friction coefficient of the coating is 0.5 at 600 ℃.The wear rate of the coating from the room temperature to 800 ℃ is lower than that of the substrate，and the lowest wear rate is 1.91×10-5 mm3/(N·m) at 400 ℃, which is about 1/3 of the substrate, indicating that the NiCrAlY/Co coating improves the high temperature wear resistance of 304 stainless steel. At medium and low temperatures， the wear mechanism of the substrate is mainly abrasive wear and adhesive wear, and the wear mechanism of the NiCrAlY/Co coating is mainly abrasive wear and gradually slight adhesive wear.At 800 ℃, the wear mechanism of the substrate is plastic deformation, and the wear mechanism of the coating is oxidation wear.